MORPHOGENETIC KEBUDAYAAN DALAM SISTEM MATA PENCAHARIAN MASYARAKAT DESA TUTUP NGISOR, KABUPATEN MAGELANG - Devi Intan Chadijah; Aan Khosihan; Irma Juraida (Jurnal Community, 2020)
Cultural systems that play an important role in people's lives, especially those related to local wisdom in the livelihoods of the people. This study aims to determine the culture of the livelihood system of Tutup Ngisor’s Village. The method in this research is qualitative with purposive sampling technique. As for conducting data validity using triangulation of sources with in-depth interviews as data collection techniques. This research was examined using structural theory and agents from Margaret S. Archer. In this theory, the morphogenetic approach can be seen in two forms, namely morphogenesis and morphostasis. There is the influence of agents and structures in interactions and actions so as to bring up structures that also react and change with the actions and interactions of the agents. Based on the findings of the field, the people of Tutup Ngisor’s Village have a number of livelihood elements that have experienced technical changes (morphogenesis) and there are some elements that have morphostatic (unchanged). Thus there is a cultural change in the livelihood systems of Tutup Ngisor’s Village community.